2002
DOI: 10.1152/ajpheart.00348.2001
|View full text |Cite
|
Sign up to set email alerts
|

Preconditioning blocks cardiocyte apoptosis: role of KATPchannels and PKC-ε

Abstract: The aims of this study were to determine whether preconditioning blocks cardiocyte apoptosis and to determine the role of mitochondrial ATP-sensitive K+(KATP) channels and the protein kinase C ε-isoform (PKC-ε) in this effect. Ventricular myocytes from 10-day-old chick embryos were used. In the control series, 10 h of simulated ischemia followed by 12 h of reoxygenation resulted in 42 ± 3% apoptosis ( n = 8). These results were consistent with DNA laddering and TdT-mediated dUTP nick-end labeling (TUNEL) assay… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
46
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 64 publications
(48 citation statements)
references
References 36 publications
1
46
1
Order By: Relevance
“…The protective actions of nitric oxide during ischemic and anesthetic preconditioning have been already demonstrated (Novalija et al, 2003a;Chiari et al, 2005b). In addition, phosphoinositide-dependent kinase 1 is a potent activator of other protein kinases, including protein kinase C, which has been implicated in the protection of myocardium against ischemia and reperfusion injury by reducing apoptosis as well as decreasing myocardial infarct size (Liu et al, 2002). Therefore, it seems that the PI3K signaling cascade may contribute to the recruitment of multiple endogenous cardioprotective pathways to reduce myocardial damage after ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…The protective actions of nitric oxide during ischemic and anesthetic preconditioning have been already demonstrated (Novalija et al, 2003a;Chiari et al, 2005b). In addition, phosphoinositide-dependent kinase 1 is a potent activator of other protein kinases, including protein kinase C, which has been implicated in the protection of myocardium against ischemia and reperfusion injury by reducing apoptosis as well as decreasing myocardial infarct size (Liu et al, 2002). Therefore, it seems that the PI3K signaling cascade may contribute to the recruitment of multiple endogenous cardioprotective pathways to reduce myocardial damage after ischemia and reperfusion.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies also indicate that cardiac ischemic preconditioning inhibits both apoptosis and necrosis. The attenuation of apoptosis is mediated by PKC-⑀ in rat hearts and chick ventricular myocytes (29,38). Cardiac reperfusion after an ischemic event also exposes myocytes to a high level of circulating nonesterified fatty acids (35,40).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast, a recent study by Liu et al [40] demonstrated that PKC-e was downstream from mitoK ATP activation in IPC's apoptosis limiting effects. Using ventricular myocytes from chick embryos, Liu and collegues reported that both IPC and diazoxide treatment reduced cardiocyte apoptosis and that both of these effects were abolished by pretreatment with specific PKC inhibitors.…”
Section: Mitok Atp Channels As a Trigger Of Ipcmentioning
confidence: 79%
“…Thus, opening of mitoK ATP channels was associated with a downstream activation of ERK. The results of Wang and Ashraf, Samavati et al, and Liu et al suggest that mitoK ATP activation may also act as a trigger of the cardioprotection [40,41,47]. Further support for this hypothesis is given by Pain et al [48].…”
Section: Mitok Atp Channels As a Trigger Of Ipcmentioning
confidence: 92%
See 1 more Smart Citation